FACTORS THAT ARE RELATED TO SUBJECTIVE COMPLAINTS OF EYE FATTY IN HEALTH CLAIM EMPLOYEES IN PT ASURANSI RELIANCE - Angeliana K, Devi; Kristina Melinda, Maria; Nitami, Mayumi; Abdul Hadi, Dudi (International Journal of Psychosocial Rehabilitation, 2020)
Eye fatigue arises as intensive stress on eye functions such as the muscles of the eye accommodation in jobs that need careful observation or on the retina as a result of inaccurate contrast. The purpose of this study is to analyze the factors associated with eye fatigue. This research is a quantitative study with a Cross-Sectional study design conducted in December 2019 - January 2020. The population and sample in this study were all employees of the Health Claim division of PT Asuransi Reliance with a total of 70 people. Research data were collected using primary data from measurements of light intensity and visual acuity as well as interviews with questionnaires. The results showed that 60 employees (85.7%) of the Health Claim Division suffered eyestrain. The most complaints are sore eyes (28.5%). Based on statistical test results it is known that the variables associated with eye fatigue are the age variable (Pvalue = 0.014), the working period variable (Pvalue = 0.014), the visual acuity variable (Pvalue = 0.011), the lighting intensity variable (Pvalue = 0.008). While gender variables are not related to subjective subjective eye fatigue (Pvalue = 0.477). To reduce the risk of eye fatigue, it is recommended that companies provide funds for eye health checks on officers, make eye rest every 1 hour of work, carry out the transfer of labor according to physical capabilities and re-arrange work room lighting